Influenza A M2 transmembrane domain tunes its conformational heterogeneity and structural plasticity in the lipid bilayer by forming loop structures. Issue 46 (23rd May 2018) - Liu, Yue; Tan, Junjun; Zhang, Jiahui; Li, Chuanzhao; Luo, Yi; Ye, Shuji
Abstract : The influenza A virus M2TM tunes its conformational heterogeneity and structural plasticity by undergoing a helix-to-loop transition. A gating mechanism coupled to the rotational motion or conformational change of the helices depends on the lipid types. Abstract : We discovered for the first time that the influenza A virus M2TM tunes its conformational heterogeneity and structural plasticity to respond to environmental cues by undergoing a helix-to-loop transition, resolving controversies regarding the mechanism of proton conduction and plasticity of the M2TM in lipid bilayers.